2023
DOI: 10.3390/met13020357
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Use of Recycled Aluminum to Generate Green Hydrogen in an Electric Bicycle

Abstract: This article proposes using recycled aluminum, generating hydrogen in situ at low pressure, to power a 250 W electric bicycle with a fuel cell (FC), to increase the average speed and autonomy compared to a conventional electric bicycle with a battery. To generate hydrogen, the aluminum–water reaction with a 6 M NaOH solution is used as a catalyst. This article details the parts of the generation system, the electronic configuration used, the aluminum- and reagent-loading procedure and the by-products obtained,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Aluminum machining scrap accounts for a significant fraction (13.7%) of the trash created by all manufacturing processes globally [ 94 ]. Waste chips and powder of that metal can be effectively ‘converted into hydrogen’ either in their original form or in the form of compacted shapes (e.g., tablets or pellets) [ 95 , 96 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum machining scrap accounts for a significant fraction (13.7%) of the trash created by all manufacturing processes globally [ 94 ]. Waste chips and powder of that metal can be effectively ‘converted into hydrogen’ either in their original form or in the form of compacted shapes (e.g., tablets or pellets) [ 95 , 96 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the incorporation of iron during the recycling process can impact the properties of the alloy, potentially limiting its reuse in the original structural application. On the other hand, to enhance the feasibility of utilizing Al alloys for hydrogen production, recycled Al alloys are preferable [32]. Eom et al [33] observed that the reaction of an Al-1Sn-1Fe alloy (wt.%) in an alkaline solution can result in a hydrogen generation rate about 6 times higher than that of pure Al and 1.6 times higher than that of the Al-1Fe (wt.%) alloy.…”
Section: Introductionmentioning
confidence: 99%